Analysis of Performance Appraisal Systems - An Empirical Evidence of Manufacturing Sector in Punjab - Saini, Dr. Ramandeep (IJRDO - Journal of Business Management, 2017)
India has witnessed an imbalanced industrial growth across different states in the past. Punjab as a state has suffered a lot due to policy induced barriers and constrained private sector initiatives through allocation of licenses and public sector investments in the industrial sector of its economy.Efforts of the subsequent governments to boost industrialization in Punjab seem to have been patronized and in recent years national and international agencies like World Bank, CRISIL, Union Government and RBI have recognized the state as a place for investments. One of the significant factors contributing to pace of industrialization is human capital of a state. The study surveyed 65 officers about performance appraisal systems being implemented in manufacturing industries of Punjab. Factor analysis and ANOVA have been used for identifying dominant variables affecting performance appraisals and the industry having the most effective appraisal systems. The results of the study can undoubtedly assist managers in developing robust performance appraisal systems